Response of cassava (Manihot esculenta Crantz) genotypes to natural infestation by scale insect pest Stictococcus vayssierei Richard (Hemiptera: Stictococcidae) - Patrice Zemko Ngatsi; Bekolo Ndongo; Zachée Ambang; Pierre Eke; William Norbert Tueguem Kuate; Sylvere Landry Lontsi Dida; Jude Ndjaga Manga; Champlain Djiéto-Lordon (Current Research in Insect Science, 2024)
Cassava is mostly grown for its starchy roots, which ensure food security. However, it is heavily attacked by the African root and tuber scale (ARTS) Stictococcus vayssierei in Central Africa. This pest is a severe constraint to the production of cassava, food and income security for smallholder farmers. Crop resistance development through the selection of varieties with resistant traits against targeted pests is a promising approach to pest control. This study investigated cassava genotypes' response to natural infestation and determined their resistance levels against S. vayssierei. Six cassava genotypes (two local and four improved) were planted in a completely randomized block design with four replicates. Agronomic parameters and ARTS density were evaluated at 3, 6, 9 and 12 months after planting (MAP). Biochemical content was determined on the pith and cortex of 12 MAP aged tuberous roots. As a result, the improved Excel variety recorded the highest scale density per plant with 102.83 ± 4.14 ARTS/P at 9 MAP. At 12 MAP, high activity of total cyanide (69.18 ± 0.88 and 69.16 ± 1.44 mg/kg) and phenylalanine ammonia-lyase (0.142 ± 0.020 and 0.145 ± 0.010 ΔA/min/mg) were observed in the cortex of the tuberous roots of the improved varieties TMS 96/0023 and TMS 92/0057 which were colonized by the lowest ARTS density. The local variety (Douma) had a high content of total phenols (44.87 ± 1.15 µg/g) in the pith. It also produced the highest yield (23.8 ± 2.9 t ha-1). Varieties TMS 96/0023, TMS 92/0057 and Douma may be the most suitable varieties for the control of ARTS stress.